Molecular basis of maintaining an oxidizing environment under anaerobiosis by soluble fumarate reductase - Sunghwan Kim (Nature Portfolio, 2018)
Soluble fumarate reductases are essential for eukaryotic cell survival under anaerobic conditions but their mechanism is not fully understood. Here, the authors present structural and enzymatic analyses of yeast fumarate reductase Osm1, elucidating the molecular basis of maintaining redox balance during anaerobiosis.